CGIAR modeling approaches for resource‐constrained scenarios: II. Models for analyzing socioeconomic factors to improve policy recommendations. Issue 2 (20th March 2020) - Kruseman, Gideon; Bairagi, Subir; Komarek, Adam M.; Molero Milan, Anabel; Nedumaran, Swamikannu; Petsakos, Athanasios; Prager, Steven; Yigezu, Yigezu A.
Abstract: International crop‐related research as conducted by the CGIAR uses crop modeling for a variety of purposes. By linking crop models with economic models and approaches, crop model outputs can be effectively used as inputs into socioeconomic modeling efforts for priority setting and policy advice using ex‐ante impact assessment of technologies and scenario analysis. This requires interdisciplinary collaboration and very often collaboration across a variety of research organizations. This study highlights the key topics, purposes, and approaches of socioeconomic analysis within the CGIAR related to cropping systems. Although each CGIAR center has a different mission, all CGIAR centers share a common strategy of striving toward a world free of hunger, poverty, and environmental degradation. This means research is mostly focused toward resource‐constrained smallholder farmers. The review covers global modeling efforts using the IMPACT model to farm household bio‐economic models for assessing the potential impact of new technologies on farming systems and livelihoods. Although the CGIAR addresses all aspects of food systems, the focus of this review is on crop commodities and the economic analysis linked to crop‐growth model results. This study, while not a comprehensive review, provides insights into the richness of the socioeconomic modeling endeavors within the CGIAR. The study highlights the need for interdisciplinary approaches to address the challenges this type of modeling faces.